Aplikasi Mobile Remote Control Bluetooth untuk Winamp - Neni Febriani; Dini Nurmalasari; Erwin Setyo Nugroho (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2011)
Abstract The mobile phone with Bluetooth devices is a technology that available in the market in the current mobile phone devices. Bluetooth technology allows users to exchange data from one device to another device without operator assistance with unlimited distance. Utilization of Bluetooth technology are now widely among the media file sharing, remote control laptop, a Bluetooth mouse (the mouse without the wires), GPS applications, and so on. One of the utilization of Bluetooth technology is the development of applications for remote control Winamp via Bluetooth mobile phone, where the application takes advantage of Bluetooth connectivity as the media handling of the control Winamp on the laptop. There are two applications that need to be installed to perform remote control of Winamp is the application on the mobile phone and the laptop. Applications on mobile phones designed using J2ME programming languages and applications on a laptop using VB programming language. NET. With this application, users can take advantage of this application to run Winamp as an alternative to using a keyboard and mouse on a laptop with a limited distance. Keywords: Remote Control Winamp, Bluetooth, mobile phone, J2ME, VB.NE